THE RISK FACTORS OF MENSTRUATION CYCLE AND LIFESTYLE TO THE PREVALENCE OF THE OVARY CYST IN GENERAL HOSPITAL DISTRICT IN KONAWE - Saraswati, Putu Suri (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2019)
Background: In Indonesia the incidence of ovarian cysts in 2015 as many as 23,400, people are expected to die as many as 13,900 people (59.40%). Preliminary studies shows that in BLUDs Konawe Hospital, Medical Records Data Obtained data on cases of ovarian cysts in 2016 as many as 57 people, in 2017 were 62 people, while In 2018, there were 87 cases.The purpose of this study was to Determine the risk factors for ovarian cysts at the Regional Public Service Board of Konawe Hospital. Methods:This is a case control study. The population of the case were all the Patients with ovarian cyst in 2018 as many as 106 people. Population control Patients were all admitted in Midwifery both outpatient and inpatient undiagnosed ovarian cyst in 2018 as many as 1,396 people. Sampling was done by simple random sampling. Controls were taken by purposive sampling method using a matching age. Data were collected through questionnaires and Analyzed using odds ratios (OR). Results: The results Showed that the odds ratio of the menstrual cycle = 2,918 and lifestyle with OR = 12 969. Therefore the value of the odds ratio (OR? 1) then all variables are risk factors for the incidence of ovarian cysts. Conclusion: Conclusion of this study is menstrual cycles and lifestyle being the risk factor to the incidence of ovarian cysts in BLUDs Konawe.